Comprehensive Medical Management of Rosacea: An Interim Study Report and Literature Review - Del Rosso, James Q. (Matrix Medical Communications, 2008)
Rosacea is a common inflammatory facial dermatosis seen in adults that exhibits considerable variety in clinical presentation. Multiple medical therapeutic options are available including topical and oral treatments. Optimal medical management of rosacea includes assessment of subtype and disease severity and use of appropriate skin care to reduce epidermal barrier dysfunction. This article provides an overall discussion of the medical management of rosacea and reviews interim results from a study evaluating the role of designated skin care in rosacea treatment.